PENELITIAN TINDAKAN KELAS : Teori dan Aplikasinya Pada Pembelajaran Bahasa Arab - Syaifudin Syaifudin (Borneo : Journal of Islamic Studies, 2021)
ABSTRACT Ideally, an Arabic teacher must have absolute empathy for the competencies that have been determined by the National Education Standards, including personal, professional, educational, and social competencies. However, after the evaluation, it is easy to master the four competencies. There are many deficiencies in the teaching-learning process, especially in the less than optimal student learning outcomes, the quality of teaching that does not answer the needs of students, and several other problems. Various types of research are offered for the study of these problems, one of which is classroom action research which is later abbreviated as PTK. PTK instructions to improve students' Arabic learning outcomes, and the quality or quality of teaching an Arabic teacher. Thus, it is necessary to have a mature concept before carrying out the PTK. To collect this concept, the authors conducted a literature study by collecting some literature in the form of journals, books, previous research, and other supporting documents. From the results of the search conducted, it was found that the concept of classroom action used to study and study linguistic fields, especially Arabic, started from a study of the urgency of the research itself which departed from efforts to improve the quality of teaching which had an impact on improving student learning outcomes. Therefore, in implementing PTK, a researcher must choose one of the models offered by the experts by going through two cycles, and of course through several stages or procedures including planning (planning), implementing (action), observation (observation), and reflection (reflection). If the procedure is passed properly, the desired results from the PTK will be realized so that it will have an impact on increasing the quality of teacher teaching and student learning outcomes.